PENYULUHAN BELA NEGARA “AKU CINTA TANAH AIR” DI SMA NEGERI 1 BAYAN LOMBOK UTARA - Marditulastri; M. Sigit Saksono (JURNAL NAGARA BHAKTI, 2022)
The Integration Training of Taruna Wreda (Latsitarda) is a momentum to build synergy between the TNI, Polri and the community. Latsitarda Nusantara is a means to foster a spirit of struggle, love for the homeland and the spirit of integration of cadets and students to build synergy and solidity of the TNI, Polri and the community. Activities carried out in this Latsitarda include physical and non-physical activities. These non-physical activities include promotion, training, counseling provided to the community and school children. The existence of moral degradation which is mostly carried out by millennials, students are marked by the erosion of polite ethics, hedonistic lifestyles, not understanding the nation's history, not knowing the nation's warrior heroes, and others. Therefore, national insight is a perspective that is surrounded by a sense of nationality, nationalism, and the spirit of nationalism in an effort to realize national ideals. The main understanding of the national insight is the awareness to unite as a nation, the existence of a common history and future interests as the glue that unites as well as provides the basis for national identity. Responding to this problem, it is necessary to rebuild the spirit of nationalism, be willing to sacrifice, awareness, unity and integrity as well as a sense of love for the homeland so that togetherness and shared responsibility grow in anticipating every form of threat. Through community service activities with the target of this school, it is hoped that the younger generation at SMA Negeri 1 Bayan Lombok Utara will cultivate an attitude of "Aku Cinta Tanah Air"